THE EFFECT OF WORK-LIFE BALANCE ON EMPLOYEE ENGAGEMENT WITH JOB STRESS AS A MEDIATING VARIABLE - Haiqal Faddel Muhammad; Kosasih (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of work-life balance on employee engagement with job stress as a mediating variable through a literature study approach. The method used is a literature review of scientific articles, national and international journals, and relevant books published between 2019 and 2025. The selected literature focuses on the relationship between work-life balance, job stress, and employee engagement. The findings indicate that work-life balance has a significant positive effect on employee engagement. Employees who maintain a balance between personal life and work tend to be more enthusiastic, loyal, and dedicated. Conversely, job stress has a negative impact on employee engagement by reducing motivation, energy, and commitment. Furthermore, work-life balance negatively affects job stress, functioning as a protective factor that reduces stress levels. These results confirm that job stress mediates the relationship between work-life balance and employee engagement. The study provides practical implications for organizations to design policies that support employees’ work-life balance, such as flexible work arrangements, organizational support, and mental health programs, in order to enhance employee engagement and organizational sustainability.